Exploratory Factor Analysis-Key to a Successful Mentoring Relationship - Jamil, N. I.; Baharuddin, F. N.; Tengku Sulaiman, T. S. R. M.; Rosle, A. N.; Harun, A. F. (Journal of Advanced Research in Business and Management Studies, 2020)
Mentoring program in various methods either in formal or informal are reputed to be beneficial for mentees, mentors, and organization. Researches and case studies of successful individuals in their careers indicate that mentoring has a profound influence on professional development. As the increment of the complexities in the workplace, there is a growing recognition that mentoring programs are needed to help individuals to be successful throughout their career development. Besides that, the organization was able to produce peers support group and creates best learning community in transferring knowledge aspect, especially in education background. This paper will examine the determinants of individuals’ advancement among the lecturers participating in mentoring program and help UiTM Negeri Sembilan to encourage academic staff to participate in mentoring systems. Exploratory factor analysis suggests that there are five determinants which account for 77.561% of the total variance with considerably reduce the complexity of the data set by using these components with 22.439% loss of information. Kaiser-Meyer-Olkin value is 0.790 and small values of the significance level of Bartlett’s test of sphericity (0.000) indicate factor analysis is feasible for this data set. Principal Component Analysis with Varimax rotation was performed and five determinants identified as essential ingredients in a successful mentor-mentee relationship denoted as career development, formal mentoring, mentoring relationship, informal mentoring and psychosocial support. Main findings suggest that the resulting of 22-items scale is much more reliable instrument than the initial 35-items scale with Cronbach’s alpha correlation coefficients of 0.913